Deliberative Democracy and the Problem of Scope - Will Friedman (Journal of Deliberative Democracy, 2006)
This article addresses the challenges of scaling up deliberative democracy beyond the level of individual communities. It begins with a general discussion of the problems that scope poses for deliberative democratic practice. It then proceeds to look critically at a range of initiatives that have, in recent years, attempted to overcome these problems in the American context. The concluding sections suggest guidelines and concepts aimed at helping practitioners approach large-scale public engagement more strategically, as well as areas that research and theory should explore.